2019
DOI: 10.1002/adfm.201902319
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Crystallization Dynamics and Grain Orientation in Sequential Deposition of Metal Halide Perovskites

Abstract: Metal halide perovskites have revolutionized the development of highly efficient, solution-processable solar cells. Further advancements rely on improving perovskite film qualities through a better understanding of the underlying growth mechanism. Here, a systematic in situ grazing-incidence X-ray diffraction investigation is performed, facilitated by other techniques, on the sequential deposition of formamidinium lead iodide (FAPbI 3 )-based perovskite films. The active chemical reaction, composition distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 47 publications
1
69
0
Order By: Relevance
“…The X-ray incident angle is set to 0.05° and 1° to probe the shallow surface and full-depth structures of the perovskite films, respectively. [39,40] The 2D GI-XRD patterns of the perovskite film taken at 1° are shown in Figure 1e-g. The GI-XRD pattern of the reference film exhibits the diffraction arcs corresponding to α-FAPbI 3 (at wavevector transfer q = 1.00, 1.41, and 1.73 Å −1 ) and a secondary phase (at q = 0.72 Å −1 ), consistent with the previous report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray incident angle is set to 0.05° and 1° to probe the shallow surface and full-depth structures of the perovskite films, respectively. [39,40] The 2D GI-XRD patterns of the perovskite film taken at 1° are shown in Figure 1e-g. The GI-XRD pattern of the reference film exhibits the diffraction arcs corresponding to α-FAPbI 3 (at wavevector transfer q = 1.00, 1.41, and 1.73 Å −1 ) and a secondary phase (at q = 0.72 Å −1 ), consistent with the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…When the X-ray incident angle is set to 0.05°, the crystallographic details of the perovskite films at shallow surface can be obtained. [39,40] Figure S2 (Supporting Information) shows the 2D GI-XRD patterns of the perovskite film taken at 0.05°. Apparently, the diffraction intensities of (PA) 2 FAPb 2 I 7 and (PDA) 3 Pb 2 I 10 are higher than those of α-FAPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…and generally mixed compositions opens a wide field for formation studies. [27][28][29][30][31][32][33] Greco et al…”
Section: Shifting From Mapbi 3 To Other Compositions Such As Fapbi 3 mentioning
confidence: 99%
“…[33] A recent study of the FAPbI 3 formation during two-step deposition by Meng et al clearly identified the photo inactive δ-FAPbI 3 as an intermediate phase in the conversion of the PbI 2 and FAI precursor to the α-phase of FAPbI 3 , as can be seen from Figure 2 (a) for the in situ XRD data and (b) for the trends in the different phases. [31] One interesting finding in the analysis of processing conditions for mixed perovskite compositions is the correlation between composition and the processing window: Qin et al found that Cs-containing compositions are less sensitive to the timing of the antisolvent deposition and therefore allow for a broader time frame for optimal deposition time. [27] As aforementioned, the antisolvent method requires delicate timing for achieving high-quality MAPbI 3 films.…”
Section: Shifting From Mapbi 3 To Other Compositions Such As Fapbi 3 mentioning
confidence: 99%
“…[26] Meng et al employed in situ GIWAXS measurements to investigate the annealing process of the PbI 2 and the perovskite, and found that adding ions of Br − , Cl − and MA + could accelerate the perovskite crystallization speed and modulate crystal grain orientations. [27] However, in situ study of the whole two-step process, especially during the two spin-coating steps, has not been reported.…”
mentioning
confidence: 99%